Gender-based violence and its associated factors among reproductive-age women in Soqota town, Amhara Region, Northern Ethiopia, 2023: A mixed study design - Yinagn Shibie Kibret; Endalkachew Worku Mengesha; Getachew Muluye Gedef; Melash Belachew Asresie (Elsevier, 2024)
Background: Gender-based violence is a human rights violation, and one in three women worldwide experiences some form of violence in their lifetime. Recently, it has received more attention, and extensive reporting systems and updated data are required. Despite this, evidence remains scarce and the case continues to be underreported. The very first step in addressing the issue is determining how prevalent gender-based violence is and the factors that contribute to it. So this study aimed to assess the prevalence of gender-based violence and its associated factors which helps to develop strategies to alleviate the problem. Methods: A community-based cross-sectional study was conducted among 403 reproductive-aged women supplemented with qualitative study from March 15th to April 15th, 2023, in Soqota town, Amhara region, Northern Ethiopia. An interviewer-administered, semi-structured questionnaire was used to collect the data. Bivariable and multivariable binary logistic regression analysis were performed to identify factors associated with the outcome variable. Variables with p < 0.25 in the bivariable analysis and a p-value of <0.05 in the final model were used to declare the level of statistical association. Qualitative data were transcribed, translated, and analyzed manually using thematic analysis. Finally, qualitative and quantitative findings were triangulated. Results: This study found that 64.8% of women experienced at least one form of gender-based violence in the past twelve months. The occurrence of GBV was significantly correlated with women's lack of education (AOR = 3.32, 95 % CI: 1.39, 7.96), primary schooling (AOR = 2.42, 95 % CI: 1.03, 5.69), poor wealth index (AOR = 2.46, 95 % CI: 1.34, 4.51), and being an employee (AOR = 0.32, 95 % CI: 0.11, 0.88). In addition, low socioeconomic status, skewed gender stereotypes, and conflict all have an impact on gender-based violence. Conclusion: The study reveals a high prevalence of gender-based violence, attributed to factors such as low education, low socioeconomic status, skewed gender stereotypes, and conflict. A comprehensive community-based health education program and the strengthening of women's empowerment are needed to tackle the issue.